Interception of a Reverse Incisor Occlusion in Mixed Dentition - Dahoue, Richard Togbedji; Houb-Dine, Afaf; Zaoui, Fatima; Benkaddour, Asmae; Benyahia, Hicham (Integrative Journal of Medical Sciences, 2022)
Introduction: This case report describes an orthodontic interception of a mixed dentition reverse incisor bite in a 12-year-old boy at the time of consultation. Case report: After a careful clinical examination supported by routine radiological examinations, a skeletal Class III diagnosis was made, and an orthodontic interception was decided to restore the inverted incisor joint and orofacial functions disrupted by the malocclusion. After 20 months of interceptive treatment consisting of a joint jump and Class III intermaxillary traction, we found satisfactory overhang and coverage, allowing us to monitor the placement of the definitive canines with an improvement in the skin profile and smile. Conclusion: This simple gesture made it possible to put the mandible back in a position restoring normal incisal coverage and contributing to good orofacial muscle maturation, which is closely linked to the restoration of various occlusal functions.